Developing Arabic language learning motivation through joyful learning: evidence from an Indonesian Islamic primary school - Oktavia, Dinda; Pranoto, Muhammad Solihin (UIR Press, 2026)
Education plays a crucial role in improving the quality of human resources. However, the learning process in schools is often perceived as monotonous by students due to the limited variety of teaching strategies and the lack of innovation in developing learning materials and instructional media. This condition may lead to low learning motivation, particularly in Arabic language learning, which requires active student engagement throughout the learning process. This study aims to investigate whether the implementation of the joyful learning method can improve the learning motivation of sixth-grade students in the Arabic language subject. This research employed a quantitative approach using classroom action research, which was conducted through the stages of planning, action, observation, and reflection. Data were collected through observation and documentation and analyzed descriptively to identify changes in students' learning motivation during the implementation of the actions. The findings indicate that the implementation of the joyful learning method successfully improved students' learning motivation, as demonstrated by increased participation, enthusiasm, attention, and active engagement during the learning process. Nevertheless, this study is limited because it was conducted in only one class at a single Islamic elementary school and relied primarily on qualitative data; therefore, the findings cannot be generalized to a broader context. The novelty of this study lies in the implementation of the joyful learning method in Arabic language instruction at an Islamic elementary school through classroom action research, providing practical evidence that enjoyable and student-centered learning can effectively enhance students' learning motivation.